Discovery of indolizines containing triazine moiety as new leads for the development of antitumoral agents targeting mitotic events. Issue 18 (15th September 2015) - Lucescu, Liliana; Ghinet, Alina; Belei, Dalila; Rigo, Benoît; Dubois, Joëlle; Bîcu, Elena
Graphical abstract